Eu receberia as piores notícias dos seus lindos lábios: linguagem e forma narrativa - Dalcin, Camila (2015)
This work aims to understand the relationship between the book, Eu receberia as piores notícias dos seus lindos lábios , from the author Marçal Aquino, and the contemporary narrative, it also tries to understand what are the consequences of this time in its discursive construction. It starts from the perspective of academic criticism to situate the novel and the author in the territory of the contemporary. Later it maps the definitions used for the literature of violence representation linked to realistic currents, from the second half of the twentieth century coming until the self titled "Generation 90", in which Marçal Aquino figures. The critique points as a symptom of this generation the incorporating of mass communication languages as an aesthetic artifact of the author to communicate his worldview. A world indeed permeated by intermedia codes, explored in this work through the image of the narrator photographer and assimilation of film language. As well as the relevance of violence resymbolization to awaken affections for a theme so dear to the contemporary Brazilian literature.